Training Programs and Staff Performance: A Case Study of Uganda Police Force - Derrick Matovu (Uganda Christian University, 2024)
The study looked on the connection between Uganda Police Force personnel performance and training initiatives. Staff performance was considered the dependent variable, and training programs the independent variable. The study set out to find out how induction training programs and staff performance in the Uganda Police Force related to each other, as well as how on-the-job training programs and staff performance in the Uganda Police Force and off-the-job training programs relate to each other. The study used a case study methodology, and questionnaires were used to gather data. The study was analyzed using both quantitative and qualitative approaches, including statistical tools for inferential and descriptive analysis. The study found a statistically significant favorable relationship between staff performance and offthe-job and introduction training programs. On the other hand, the study found a positive statistically non-significant association between staff performance and on-the-job training programs. The study makes the following recommendations for the Uganda Police Force: it should prioritize new hires and promotions, maintain senior management's coaching of junior staff to improve performance, place more emphasis on seminars, resource person lectures, and distance learning, and take into account other factors like leadership, supervision, and policy issues to improve staff performance in addition to training programs.